2020
DOI: 10.1177/2325967120964622
|View full text |Cite
|
Sign up to set email alerts
|

Hand and Wrist Injuries Among Collegiate Athletes: The Role of Sex and Competition on Injury Rates and Severity

Abstract: Background: There is a high incidence of hand and wrist injuries in athletes participating in collegiate sports, but there is little information published characterizing them. Purpose: To characterize hand and wrist injuries in collegiate athletes using a large national database. Study Design: Descriptive epidemiology study. Methods: This retrospective cross-sectional analysis was designed using data from the National Collegiate Athletic Association (NCAA) Injury Surveillance Program database to identify hand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Previous studies have reported the epidemiology of hand and wrist injuries in NCAA football players. 1,2,5,13 Bartels et al 1 reported the epidemiology of hand and wrist injuries in collegiate football players over 5 athletic seasons (2009-2010 to 2013-2014), using data from the NCAA ISP. The authors reported a significantly higher incidence rate of hand and wrist injuries during competitive matches compared with practice (3.6 vs 0.51 injuries per 1000 AEs, respectively) in football players competing in all 3 NCAA Divisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported the epidemiology of hand and wrist injuries in NCAA football players. 1,2,5,13 Bartels et al 1 reported the epidemiology of hand and wrist injuries in collegiate football players over 5 athletic seasons (2009-2010 to 2013-2014), using data from the NCAA ISP. The authors reported a significantly higher incidence rate of hand and wrist injuries during competitive matches compared with practice (3.6 vs 0.51 injuries per 1000 AEs, respectively) in football players competing in all 3 NCAA Divisions.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,14,15 The majority of descriptive epidemiological studies analyzing hand and wrist injuries in collegiate football players use data from the NCAA ISP, which lacks clinical details including specific diagnoses, type, and duration of immobilization, and surgical procedures performed. 1,4,5,13 More detailed clinical data on the management and outcomes of hand and wrist injuries in collegiate football athletes are available mostly through small case series and case reports. 2,3,6,7,9,16,17 In addition, the risk factors for surgical intervention and those related to early or delayed time to return to play (RTP) have not been investigated.…”
mentioning
confidence: 99%
“…Our recent publication studied the epidemiology of such injuries across major collegiate sports stratified by gender and competition. We revealed that male athletes experience injuries with more frequency and severity than female athletes and injuries were more likely to occur in competition than practice (Simpson et al 2020 ). Our results have been supported by other publications evaluating the epidemiology of varying injuries using the ISP (Dalton et al 2015 ; Fraser et al 2017 ; Kerr et al 2011 ; Zuckerman et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This change in injury reporting was uniform across all divisions and genders, so this change should not affect the findings of the study. The two eras have been combined in similar analyses previously (Simpson et al 2020 ; Kerr et al 2014 ; Chorney et al 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation